Three-Dimensional Speckle-Tracking Echocardiography-Derived Left Ventricular Global Longitudinal Strain and Mitral Annular Plane Systolic Excursion Are Associated in Healthy Adults—Insights from the MAGYAR-Healthy Study - Nemes Attila; Ambrus Nóra; Lengyel Csaba Attila (2025)
Introduction: Mitral annular plane systolic excursion (MAPSE) is a quantitative feature of left ventricular (LV) function that can be easily measured by M-mode echocardiography. The more recent LV strains represent LV contractility, and they can be determined for the three main directions in the radial (RS), longitudinal (LS), and circumferential (CS) directions. Three-dimensional (3D) speckle-tracking echocardiography (3DSTE) seems to be ideal for the simultaneous assessment of all LV strains from the same acquired 3D dataset. Their associations, however, have not been fully analyzed in clinical settings in healthy volunteers yet. Therefore, the present study aimed to find associations between MAPSE and 3DSTE-derived LV strains in healthy circumstances. Methods: The present study consisted of 106 healthy adult volunteers (mean age 28.1 ± 6.3 years, 48 men). Complete two-dimensional Doppler echocardiography with MAPSE assessment and 3DSTE-derived LV strain measurements were performed in all cases. Results: Tendentiously reduced LV volumes with preserved LV ejection fraction were present in the case of mean MAPSE as compared to decreased/increased MAPSE. Global and regional LV-RS and LV-CS did not differ if MAPSE was increased, mean or decreased. Global LV-LS was reduced in the case of decreased MAPSE, mainly due to tendentiously higher apical LV-LS. MAPSE did not differ if global LV-RS and LV-CS were increased, mean or decreased. MAPSE was tendentiously increased in the presence of increased global LV-LS. Conclusions: Only 3DSTE-derived global LV-LS and MAPSE are associated in healthy adults; LV global strains in other directions show no relationship with MAPSE.
Keywords: Klinikai orvostan